Self-perception evolution among university student TikTok users: evidence from China - Zhu, Jinsheng (Jason); Ma, Yan; Xia, Guoen; Salle, Sabariah Mohamed; Huang, Hongye; Sannusi, Shahrul Nazmi (Frontiers in Psychology, 2024)
This article is part of the thesis dissertation of the author form the Faculty of Social Science, Universiti Kebangsaan Malaysia. This article is part of academic achievements of Research Project of the Ministry of Educaiton of China in Humanities and Social Sciences: A Study on the Use of Social Media and the Connotation of Chinese Ethnic Community Consciousness among Ethnic Minorities in the Southwest Border Areas (22YJC860023); New Liberal Arts Research and Reform Project of Ministry of Education of China: Exploration and Practice of ASEAN International Management Applied Talents Cultivation under the Background of New Liberal Arts (No. 2021110077) and Guangxi Higher Education Undergraduate Teaching Reform Project (No. 2021JGZ153). This article is part of academic achievements of first-class universities and disciplines in tourism management discipline (project) in Guangxi, China. The corresponding author has also been participating in research projects supported by Guilin Tourism University-China ASEAN Research Centre.